The changing landscape in nephrology education in India - Vali, P. S.; Parikh, Namrata; Mohan, Krithika; Anandh, Urmila (Frontiers in Nephrology, 2023)
Digital tools have revolutionized education in nephrology in India. All forms of in-person learning are moving online. Social media have taken over the world, with clinicians learning and promoting multidirectional education methods. E-learning is better equipped to keep up with the rapid pace of new knowledge generation and dissemination. The use of digital multimedia tools to enhance rapid learning is backed by science, viz., dual-coding theory. Digital tools such as Twitter, blogs, podcasts, YouTube, and Nephrology Simulator (NephSIM) have had an impact in facilitating nephrology education among medical professionals and the general public. Digital tools, such as NephMadness, have resulted in the gamification of nephrology learning. Social media usage by the nephrology community in India is growing at a rapid pace. Everyday Cases in Nephrology (#ECNeph), a monthly Twitter-based discussion focused on academically challenging clinical cases, has its origins in India. The Women in Nephrology, India (WIN-India) initiative is very active in facilitating digital education in India and has, in a short space of time, created phenomenal momentum. Furthermore, non-governmental organizations in India, such as the Kidney Warriors Foundation and the Multi Organ Harvesting Aid Network (MOHAN) Foundation, have successfully tapped into social media to educate and aid kidney disease patients. All technologies come with some drawbacks. Despite their acceptance and validation, digital tools have their own pitfalls. These relate to (1) accessibility and connectivity, (2) accuracy of the scientific information, (3) social media noise, and (4) patient privacy. All pitfalls of digital education can be addressed by avoiding excessive social media overload and adopting an appropriate peer-review process. It is advisable to seek written consent from patients whenever patient data are posted online, to avoid privacy issues.